Antioxidant capacity of Livistona saribus fruit / Alia Adil Shah - Alia , Adil Shah (2017)
Livistona saribus shares similar family to L. chinensis which has been consumed by the C hinese and Japanese in maintaining general health. Therefore, the aim of this study is to assess L. saribus’s fruit antioxidant capacity which has not been studied before. The determination of antioxidant capacity was assessed in vitro and in vivo. Four (4) kinds of L. saribus extracts for both coat and seed; hexane, chloroform, methanol and water, were subjected to in vitro evaluation specifically, total phenolic content (TPC), total flavonoid content (TFC), DPPH radical scavenging, ferric reducing and ferrous chelation. In vitro results suggest that each fraction exhibits different antioxidant mechanism, since the antioxidants results were varied according to type of extracts and fruit parts (coat and seed). Tandem liquid chromatography and mass spectrometry (LC-MS/MS) assessment had identified that water seed fraction contains 2(3,4-dihyroxyphenyl)-7-hydroxy-5-benzenepropanoic acid and oxooctadecanoic acid, which are phenolic acid and stearic acid respectively that are purportedly contribute to its antioxidant action. Meanwhile, in vivo analysis utilising water seed fraction on Sprague Dawley (SD) rats suggests that 300 mg/kg body weight extract supplementation and oxidative stress induced, Group 4 heightened SOD activity and catalase activity that led to protection against lipid peroxidation. This preliminary analysis of L. saribus antioxidant capacity paved the way to new discoveries of potent antioxidant in health supplementation industry. The possible antioxidant mechanism of action of L. saribus extract includes its ability to scavenge reactive oxygen species or/and enhance endogenous antioxidants levels. At present study we have found that L. saribus has the ability to enhance the levels of an important intracellular antioxidant.